The anger that moves. The affirmative dimension of rage in the Italian movement against gender violence Lucha y Siesta - Mandolini, Nicoletta (2021)
Rage and anger have largely been seeing as disruptive, disquieting and threatening emotions. Often tied to violence or classified as personal negative reactions, these feelings constitute a taboo especially for women. In line with recent theoretical efforts to qualify rage as a prolific emotion for feminist politics (Traister 2018; Chemaly 2018), this paper (re)considers rage as a tool that triggers alternative political actions to address systemic injustices through non-conventional modes of protest. Starting with a consideration of feminist’s accounts of rage (Braidotti 2017) and its political uses (Lorde 1984), we will look at how rage has guided feminist interventions against gender-based violence in contemporary Italy, paying particular attention to resistance practices and discourses developed by movements for the maintenance of bottom-up services of women’s shelters in Rome, the Italian capital. The aim of this paper is to think of anger as a “heretical and generative idea” (Lorde 1984: 129) that serves the purposes of political change. To do so, we will look at the experience of Lucha y siesta, a feminist Roman collective that supports survivors of domestic abuse, recently threatened with eviction. After the local administration decided to sell the buildings where the collective run its projects, Lucha y siesta started an extensive campaign based on public engagement and the work of comic artists and illustrators. The collective prompted artists from all over Italy to create images and posters with collages of joyfully angry luchadoras (epithet used in Mexico to indicate women wrestlers) and affixed them on the walls of many Roman neighbourhoods. Meanwhile, “luchadoras-masks” were distributed online to facilitate a bottom-up, diffused and creative participation to the protest. While rage and anger, undoubtedly, dominate Lucha y siesta’s political operation (as the figure of the luchadora suggests), these feelings reclaim a space without resorting to violence, nor to traditional ways of dissent. Rather, in intermingling material and virtual practices, the strategies adopted by Lucha y siesta to counteract gender violence and the institutions that legitimise it, convey anger and rage by capillary spreading around the city a powerful demand to be heard and seen. The figure of the luchadora lets the fury explode in a mockery of the typical wrestler and in the creation of a new urban landscape where each wall can become the stage for rage while every person can dress their dissent up by wearing the mask to endorse Lucha y siesta’s cause.